Performance Analysis of Extraction Machine Using Ohmic Technology for Producing Anthocyanin - Yusron Sugiarto; Khoirul Anam Asy Syukri; Anang Lastriyanto; Yusuf Hendrawan (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2023)
Extraction is one of the important processes for obtaining anthocyanins as natural dyes. The aim of this study is to investigate the performance of the extraction apparatus using ohmic technology to produce anthocyanins. This study used a series of ohmic heating consisting of tubular pipes with a diameter of 6 cm and a length of 5.5 cm with a volume capacity of 100 ml. This extraction machine was completed with two electrodes that each have a thickness of 10 mm. The performance of extraction machines using ohmic technology was analyzed by using various voltages of 20, 30, 40, 50, and 60 Volts/cm. The result showed that the voltage affected the electric current of the machine. The voltage of 60 Volts/cm was able to produce the largest average electric current of 5.28 A with the greatest electric current achievement of up to 6.21 A. The result showed that increasing the voltage during the extraction process reduced the time needed to reach the expected temperature. The fastest time was achieved in the voltage of 60 Volts/cm with an average time of 11.3 seconds. The increased voltage in the extraction treatment also affects the total anthocyanin produced. The highest total anthocyanin was obtained from a voltage gradient of 60 Volts/cm with a value of 288.014 mg/L and a yield of 14.4%.